The effect of rapid and gradual weight loss on some hematological parameters in trained wrestlers - Ghaemi, J.; Rashidlamir, A.; Attarzadeh, S. R. (International Journal of Wrestling Science, 2014)
Introduction: Weight loss is a common issue among athletes, especially wrestlers. It is important that the various methods of weight loss be studied relative to the effect on athletic performance as well as the athletes' immune systems. The purpose of this study was to compare the effects of rapid and gradual weight loss methods on white blood cells in trained wrestlers.